Criminal Punishment for Perpetrators of Sexual Crimes in Indonesia as Reviewed by Law Number 12 of 2022 Concerning Criminal Acts of Sexual Violence (Study of Judgments Number 73/PID.SUS/2023/PN MDN and Number 1448/PID.B/2023/PN MDN) - Ricky Martin Sihombing; Marlina Marlina; Wessy Trisna; Grace Prima Apriani Sihombing (Transpublika Publisher, 2025)
The Law on Sexual Violence constitutes a lex specialis provision in relation to the Criminal Code and other statutory instruments governing offenses of a sexual nature. Sexual offenses represent a category of crime encompassing diverse manifestations and demonstrating a continuous upward trajectory annually. The promulgation of this legislation is intended both as a mechanism to instill a preventive and punitive impact upon offenders and as a safeguard to ensure the protection of individuals subjected to sexual victimization. This inquiry employs a normative-juridical mode of legal scholarship with a descriptive-analytical orientation, utilizing a legislative framework approach in conjunction with a conceptual perspective. The research techniques applied encompass a bibliographic exploration alongside an empirical dimension, the latter undertaken through direct dialogues with members of the judiciary. From the findings and deliberations presented in this thesis, it can be inferred that legal provisions governing criminal acts of sexual violence, though previously dispersed across multiple statutory instruments, are now comprehensively consolidated under Law Number 12 of 2022 concerning Crimes of Sexual Violence. The imposition of criminal liability upon offenders of sexual crimes necessitates the fulfillment of three essential elements: the presence of fault, the capacity for accountability, and the absence of exculpatory grounds, with criminal sanctions expressly guided by the aforementioned law. Furthermore, an examination of Medan District Court Decisions No. 73/Pid.Sus/2023/PN Mdn and No. 1448/Pid.B/2023/PN Mdn shows that Law No. 12 of 2022 is not yet optimally enforced, especially in sentencing, restitution, and rehabilitation.